A Surviving Child from Acute Liver Failure after an Ingestion of Cassia occidentalis Seeds. (23rd November 2020) - Getsuwan, Songpon; Tanpowpong, Pornthep; Trakulsrichai, Satariya; Sornmayura, Pattana; Treepongkaruna, Suporn
Abstract: Cassia occidentalis toxicity is thought to be uncommon; however, several cases have been described with acute hepatomyoencephalopathy with a high-mortality rate. We report a previously healthy, 2-year-old girl who developed acute liver failure after fresh seed ingestion. Without a specific antidote, we decided to implement supportive measures and medications including lactulose, sodium benzoate and N-acetylcysteine. The patient also experienced with cardiogenic shock and transient distal renal tubular acidosis, which were all spontaneously resolved. The liver chemistries returned to normal 3 months after the ingestion, without receiving liver assisted device or liver transplantation.